Some issues of the use of information and communication technologies in the digitalization of the economy of the regions of Kazakhstan - Sabyrzhan, A.; Ayaganova, M.P.; Toleuuy, A.; Jumabayeva, Sh.B. (BUKETOV BUSINESS REVIEW, 2021)
Object: To propose ways of development of the economy digitalization in Kazakhstan regions by applying the analysis of the state of use of information and communication technologies in it. Methods: The methodological basis of the study is scientific methodological approaches and research methods, such as comparison, grouping, analysis, classification, statistical methods, induction, deduction, modeling and economic and mathematical methods. Results: In order to increase the demands and proposals for information and communication technologies, interaction between enterprises of the main industry and local information and communication technology companies (IT forums, days of digitalization, hackathons, etc.) needs to be implemented, considering regional technology parks, laboratories and incubators as an opportunity to target the main regions. Conclusions: Considering the growing trend towards digitalization of economic sectors and the introduction of elements of Industry 4.0 in Kazakhstan, it is expected that Kazakhstani IT companies will be involved in this field. This will increase the gross value added of the information and communication technology industry, reduce the cost of implementing various systems in production and increase the competence of the local IT market for the subsequent export of its own developments. On the basis of information and communication technologies, assessing the problems of digitalization of the economy, examining the results of the analysis of the use of information and communication technologies in the digitalization of the regional economy, we suggest ways of developing of information and communication technologies in the digitalization of the economy of the regions of Kazakhstan.